A Nanocomposite of Bismuth Clusters and Bi2O2CO3 Sheets for Highly Efficient Electrocatalytic Reduction of CO2 to Formate. Issue 3 (7th December 2022) - Lin, Li; He, Xiaoyang; Zhang, Xia‐Guang; Ma, Wenchao; Zhang, Biao; Wei, Diye; Xie, Shunji; Zhang, Qinghong; Yi, Xiaodong; Wang, Ye
Abstract: The renewable‐electricity‐driven CO2 reduction to formic acid would contribute to establishing a carbon‐neutral society. The current catalyst suffers from limited activity and stability under high selectivity and the ambiguous nature of active sites. Herein, we report a powerful Bi2 S3 ‐derived catalyst that demonstrates a current density of 2.0 A cm −2 with a formate Faradaic efficiency of 93 % at −0.95 V versus the reversible hydrogen electrode. The energy conversion efficiency and single‐pass yield of formate reach 80 % and 67 %, respectively, and the durability reaches 100 h at an industrial‐relevant current density. Pure formic acid with a concentration of 3.5 mol L −1 has been produced continuously. Our operando spectroscopic and theoretical studies reveal the dynamic evolution of the catalyst into a nanocomposite composed of Bi 0 clusters and Bi2 O2 CO3 nanosheets and the pivotal role of Bi 0 −Bi2 O2 CO3 interface in CO2 activation and conversion. Abstract : An electrocatalyst derived from Bi2 S3 is very powerful for the reduction of CO2 to formic acid, achieving a current density of 2.0 A cm −2 with a formate Faradaic efficiency of 93 % and a single‐pass formate yield of 67 %. The active catalyst is composed of Bi nanoclusters on Bi2 O2 CO3 nanosheets and the interfacial Bi site plays a pivotal role.